2021
DOI: 10.1089/whr.2021.0105
|View full text |Cite
|
Sign up to set email alerts
|

Elements of Pregnancy and Parenthood Policies of Importance to Medical Students and Included in a Sample of Medical Schools' Websites and Student Handbooks

Abstract: Background: Medical students who are parents or considering parenthood often want information about school policies. An earlier survey of 194 medical students from one U.S. school examined seven “elements that [students thought] should be included in a school policy on pregnancy/maternity leave.” For example, students want to know “how much time a student can take off during medical school and still graduate with their class.” We performed multivariate and multivariable analyses of the University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Overall, there was a lack of documentation and formalized processes related to the support of this group of students. Although the findings presented here are specific to the ANZ context, they resonate with those reported by others, [7][8][9] and with a cohort of up to 10% of medical students commencing medical school with parenting responsibilities or becoming parents during medical school, this is an area which requires attention.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Overall, there was a lack of documentation and formalized processes related to the support of this group of students. Although the findings presented here are specific to the ANZ context, they resonate with those reported by others, [7][8][9] and with a cohort of up to 10% of medical students commencing medical school with parenting responsibilities or becoming parents during medical school, this is an area which requires attention.…”
Section: Discussionsupporting
confidence: 88%
“…Augmenting existing policies with procedures to provide an explanation of how to apply a leave policy to the medical school context would avoid the risk of sending a message to students that entry-to-practice medical courses may not recognize, support or assist them to fulfil their needs during pregnancy or as parents. Studies in the United States 8 , 9 and internationally 17 , 18 have surveyed medical students’ perspectives of what they consider the key characteristics of family-friendly medical schools. These found that despite cultural and geographic differences, students consistently reported they wanted schools to provide clear and reliable information regarding leave for students who are pregnant or parents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations